PENGARUH SUSUNAN DAN JUMLAH LUBANG BAUT TERHADAP KEKUATAN RANGKA MAIN LANDING GEAR UNTUK PESAWAT UAV - Lasinta Ari Nendra Wibawa (Universitas Sultan Ageng Tirtayasa, 2019)
This study examined the effect of the arrangement and number of bolt holes on the strength of the main landing gear frame for UAV aircraft using the finite element method. Linear static analysis was carried out using Autodesk Inventor Professional 2017 software. Main landing gear frame using Aluminum alloy 5083. Variable arrangement and number of bolt holes were 3 bolts (series), 3 bolts (zigzags), 4 bolts (series), 4 bolts (zigzags) ), 5 bolts (series), and 5 bolts (zigzags). The simulation results show that the safety factor is for the arrangement and the number of bolts 3 bolts (series), 3 bolts (zigzags), 4 bolts (series), 4 bolts (zigzags), 5 bolts (series), and 5 bolts (zigzags) were 3.498, 3.325, 3.843, 3.793, 3.401, and 3.338.